Regional Inventory Approach for Paddy Plantation Area Estimation at Yogyakarta Special Province - Noorhadi Noorhadi; Su Ritohardoyo (Forum Geografi, 2002)
Generally agricultural data could be collected by several techniques, i.e. rural statistic, sensus, administrative by product, multiple frame sampling  surcey, and frame sampling survey regional inventory. However this research aim was stressed on applying of regional inventory for estimating of rice planting area. This research was carried out in Yogyakarta Special Region. Survey method was employed by data collecting from field observation of land cover on seleted area sample. Proportion of the land over was extrapolated for grasping every kind of land covers on population area. Several steps of research are land stratification, composting of frame sampling, segment sample extraction, field works, and data analysis. Digital Map of Rie Field Standard sacle 1:100.000 used for land stratifying, result three polygons are wetland arable, dry land arable, and highland arable. Based on the frame sampling and its extraction used Systemic Aligned Random Sampling, were selected 53 segment sample distributed in 32 sub districts. Data analysis was performed through desriptive technnique in which mathematically analysis was mmostly used. Result of the research indicates that the regional inventory approach is suitable enough for estimation of rice planting area. However several modifications need to be adapted to the region characteristic. The result of the estimatio shows that the rice planting area on the first period since land preparation up to harvest season (May 2002) is 23,694 ha. Generative phase of rice planting is dominant on the riice field. This phase indicates that the area prediction of rice harvest on July 2002 is about 10,028 ha. The acumulative area of rice harvest on period May – September 2002 is estimated about 22,269 ha. The result of this research finds out that the rice planting area on the second period (July 2002) is predicted about 12,780 ha. On this period, the area is dominated by the phase of rice harvest about 7,015 ha. Based on the rice planting area at phase generative on this period can be predicted that rice harvest area up to September 2002 is about 2,743.7 ha. The acumulative area of rie havest on period July up to the end of November 2002 is estimated about 5,764.87 ha. In generally, regional inventory approach is suitable for estimating for rice planting area.